Molecular Detection and Identification of Babesia spp., Theileria spp., and Anaplasma spp. in Sheep From Border Regions, Northwestern China - Li, Yongchang; Galon, Eloiza May; Guo, Qingyong; Rizk, Mohamed Abdo; Moumouni, Paul Franck Adjou; Liu, Mingming; Li, Jixu; Ji, Shengwei; Chahan, Bayin; Xuan, Xuenan (Frontiers in Veterinary Science, 2020)
Babesia, Theileria and Anaplasma are important causative agents of tick-borne diseases that severely affect sheep. However, there is paucity in the occurrence genetic diversity of the infections of tick-borne diseases in sheep in border regions, northwestern China. In this study, nested polymerase chain reaction (nPCR) assays and gene sequencing were used to identify tick-borne Babesia spp., Theileria spp. and Anaplasma spp. infections in northwestern China. Out of 323 samples tested in this study, 225 (69.7%) sheep were infected with Babesia spp., Theileria spp. and Anaplasma spp.. Two hundred six (63.8%), 60 (18.6%), 54 (16.7%), 51 (15.8%), 32 (9.9%), 19 (5.9%), 16 (5.0%) were positive for A. ovis, B. motasi-like, A. bovis, T. uilenbergi, A. phagocytophilum, T. luwenshuni and B. motasi-like Xinjiang, respectively. The most common dual infection was with A. ovis and B. motasi-like while the most frequent triple coinfection was A. ovis, B. motasi-like and T. uilenbergi with coinfection rates of 17.0% (55/323) and 5.0% (16/323), respectively. Sequencing analysis indicated that A. ovis MSP4, A. phagocytophilum epank1, A. bovis 16S rRNA, B. motasi-like rap1-b, B. motasi-like Xinjiang rap1-a, T. luwenshuni 18S rRNA and T. uilenbergi 18S rRNA from border regions, northwestern China, showed 99%-100% identity with documented isolates from other countries. To the best of the authors’ knowledge, this is the first report of T. uilenbergi and T. luwenshuni infections of sheep in border regions, northwestern China. Furthermore, these findings provide important data for understanding the distribution of Babesia, Theileria and Anaplasma in sheep between border countries and China.